The history and current applications of the circular economy concept. (February 2017) - Winans, K.; Kendall, A.; Deng, H.
Abstract: The challenges of balancing industrial development, environmental and human health, and economic growth in China and elsewhere in the world are drivers for recent resource use and low-carbon development strategies that include the application of the circular economy (CE) concept. A central theme of the CE concept is the valuation of materials within a closed-looped system with the aim to allow for natural resource use while reducing pollution or avoiding resource constraints and sustaining economic growth. The objectives of this study are (1) to review the history of the CE concept to provide a context for (2) a critical examination of how it is applied currently. Thematic categories are used to organize the literature review results including policy instruments and approaches; value chains, material flows, and products; and technology, organizational, and social innovation. The literature review illustrates the variability in CE project success and failure over time and by region. CE successes, key challenges, and research gaps are identified. The literature review results provide useful information for researchers as well as multi-stakeholder groups who seek to define the CE concept in practical terms, and to consider potential challenges and opportunities it presents when implemented.